Leong's manual of diagnostic biomarkers for immunohistology - Chetty, Runjan ca. 20./21. Jh; Cooper, Kumarasen ca. 20./21. Jh; Cheung, Carol ca. 20./21. Jh; Mandavilli, Srinivas ca. 20./21. Jh (Cambridge medicine (Series), 2022)
With the interest in biomarkers available for diagnostic, therapeutic, prognostic and research applications growing rapidly, it is now expected that every pathologist should be aware of the correct application of immunohistochemistry in daily practice. This fully updated fourth edition provides practical guidance about preparation, key uses and pitfalls of antibodies for immunohistology in a unique A-Z format. Seventeen full colour infographics present detail about specific biomarkers, including FOXL2, GATA3 and SOX10, pulling out information about expression in tissues and prognosis. Expanded with new biomarkers and the removal of biomarkers that are no longer in common use, each entry in this concise new edition follows a standard structure for quick and easy access by busy readers